Analisis Peran Aktor dalam Kebijakan Kemandirian Petani Konservasi Lahan melalui Program Flood Management in Selected River Basins (FMSRB) - Agus Lukman Hakim; Pryo Handoko; Arif Nugroho; Natta Sanjaya; Ade Hadiono; Ipah Mulyani; Nasir Nasir; Siti Aina Firdaus (Jurnal Administrasi Publik, 2023)
This study analyzes the role of actors in farmer institutional strengthening policies as an implementation of the Flood Management In Selected River Basins (FMSRB) Program that has been accompanied and fosters independence in funding farmer groups. The informants of this research were all farmer groups who received benefits from the Community Driven Development (CDD) program in the Farmland Management and Sustainable Agriculture Practices for Flood Management in Selected River Basins Sector Project – FMSAP FMSRB Pandeglang Regency as well as policy stakeholders and competent experts in the program with a total of 22 people.  Data analysis using Stakeholder Analysis. Based on stakeholder analysis, it was found that first, the main actor is the farmer group as the beneficiary, the relationship and influence are very strong because as the object of the beneficiary The secondary stakeholders are academics, mass media, private sector, consultants, CF (Facilitator), Extension (PPL), Communities are affected indirectly, with the actors most playing a role being private actors. Key stakeholder groups include donor agencies, the Asian Development Bank; the ministry of agriculture and related ministries such as the Environment; Local Government of Pandeglang Regency, especially the Department of Agriculture and Food Security; Regional Development Planning Agency; Regional Financial Revenue and Assets Agency; Environmental Agency; Regional Disaster Management Agency; Department of Public Works and Spatial Planning. The initiator and catalyst actors in the sustainability of the program are highly dependent on the Regional Government of Pandeglang Regency, especially the Department of Agriculture and Food Security. Second, the pattern of Sustainability and Development of FMSRB is expected to be initiated by the Pandeglang Regency Agriculture and Food Security Office by involving various agencies and community groups concerned with land conservation efforts.